2016
DOI: 10.3892/ol.2016.5309
|View full text |Cite
|
Sign up to set email alerts
|

Skin toxicity in a patient with ovarian cancer treated with pegylated liposomal doxorubicin: A case report and review of the literature

Abstract: Abstract. Pegylated liposomal doxorubicin (PLD) is a form of doxorubicin enclosed in pegylated liposomes. In contrast to conventional doxorubicin, PLD is characterized by a lower incidence of cardiotoxicity and myelosuppression. However, it induces specific mucocutaneous side effects, particularly palmar-plantar erythrodysesthesia (PPE). Other dermal manifestations, such as intertrigo-like dermatitis, diffuse follicular rash, melanotic macules, maculopapular rash or recall phenomenon are less common. Mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
(17 reference statements)
1
21
0
1
Order By: Relevance
“…Pegylated liposomal doxorubicin is used to treat both ovarian cancer and AIDS‐related Kaposi's sarcoma in Japan. The most common cutaneous adverse effect induced by PLD is HFS, which usually occurs within 2–12 days after the administration of PLD . A previous study found that approximately 0.08% of patients showed intertrigo‐like reactions after taking PLD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pegylated liposomal doxorubicin is used to treat both ovarian cancer and AIDS‐related Kaposi's sarcoma in Japan. The most common cutaneous adverse effect induced by PLD is HFS, which usually occurs within 2–12 days after the administration of PLD . A previous study found that approximately 0.08% of patients showed intertrigo‐like reactions after taking PLD .…”
Section: Discussionmentioning
confidence: 99%
“…Pegylated liposomal doxorubicin (PLD), an anthracycline‐based drug, is a form of doxorubicin enclosed in pegylated liposomes. Although PLD is associated with a lower incidence of cardiotoxicity and myelosuppression, it is associated with a higher risk of dermal disorders and specific mucocutaneous side‐effects when compared with conventional doxorubicin . Common PLD dermal disorders include hand–foot syndrome (HFS), intertrigo‐like eruptions, a diffuse follicular rash, melanotic macules, a maculopapular rash and recall phenomenon .…”
Section: Introductionmentioning
confidence: 99%
“…Skin lesions usually appear in regions prone to trauma such as the palms and soles. This was reported in a patient suffering from ovarian cancer showing partial response to chemotherapy [61].…”
Section: Cytotoxicity Rendered By Liposomesmentioning
confidence: 99%
“…These PEGylated liposomes show a lower rate of cardiotoxicity and myelosuppression but show some obvious adverse effects including palmar-plantar erythrodysesthesia (PPE and some dermal manifestations such as intertrigo-like dermatitis, diffuse follicular rash, melanotic macules, maculopapular rash [61]. Some studies have advocated that dimethyl sulfoxide or corticosteroids may be beneficial in the treatment of PLD-induced dermal complications as they accelerate skin recovery.…”
Section: Pegylated Liposomal Doxorubicin (Pld)mentioning
confidence: 99%
“…The chemotherapeutics subsequently spread on the skin surface as if topically applied and re‐penetrate into the upper skin layers . Here, they can lead to radical formation and inflammatory or toxic skin effects, including development of palmar‐plantar erythrodysaesthesia, also known as a hand‐foot syndrome …”
Section: Introductionmentioning
confidence: 99%